Eco Enzyme As a Means of Environmental Conservation Education in Understanding Events 2:15 - Ekoprodjo, Herman Sjahthi; Wibowo, Markus (Peneliti.net, 2024)
Based on the meaning of Genesis 2:15, this paper talks about the use of eco enzyme as a way to teach people about environmental conservation. Eco enzyme is a natural mixture of organic waste mixtures that can be used to clean the environment in an environmentally friendly way. By understanding God's message to man to cultivate and care for the Earth (Genesis 2:15), the use of eco enzyme can be a practical way to educate Christians to do what they should do to protect the environment.